Jesus revela o Abbá: uma reflexão teológica da paternidade divina e da vivência da filiação - Biancão, Ronivalder (2024)
The present work aims a theological investigation regarding divine paternity and the experience of filiation in the face of the postmodern context of criticism of the paternal reference and the image of God. This research has two chapters, so the first one is an archaeological exposition that aims to provide readers with an accurate data regarding the notion of divine paternity that was developed over time in the Judeo-Christian universe. The second one deals with the status quaestionis of the issue surrounding the paternal symbol, its incidences and consequences for the Christian image of God the Father, as well as the application of a new biblical hermeneutics developed by the theologian Andrés Torres Queiruga that intends to collaborate on restoration of the paternal image of God and to indicate ways of experiencing filiation in the light of a new paradigm of revelation